ANALISIS SWOT STRATEGI PEMASARAN ASURANSI JIWA AJB BUMI PUTERA 1912 - Sri Handayani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
Sri Handayani ; Today's business growth in the life insurance sector in Indonesia continues to improve, but to learn from the experience of the banking sector, it should be examined whether the existence of the businesses owned nationwide in the life insurance sector becomes desperate and lost market share in the country to deal with businesses that come from overseas managed to win greater trust from the buyers insurance protection services. This study aimed to analyze the strengths and weaknesses in the face of opportunities and threats of life insurance marketing strategy AJB Bumiputera 1912 Bengkulu. The sample in this study is the assumption of an effective strategy to maximize the strengths and minimize the weaknesses of the company and the opportunities and threats. The method used is the SWOT analysis. These results indicate that the AJB Bumiputera 1912 Bengkulu workable strategy is a strategy of horizontal integration, cost efficiency and the use of high technology to the payment system and insurance product ordering system, all of this should be directed to customer satisfaction.Keyword: SWOT Analysis, Marketing Strategy